Mending a broken heart: the role of mitophagy in cardioprotection - Moyzis, Alexandra G. (Am J Physiol Heart Circ Physiol, 2014)
The heart is highly energy dependent with most of its energy provided by mitochondrial oxidative phosphorylation. Mitochondria also play a role in many other essential cellular processes including metabolite synthesis and calcium storage. Therefore, maintaining a functional population of mitochondria is critical for cardiac function. Efficient degradation and replacement of dysfunctional mitochondria ensures cell survival, particularly in terminally differentiated cells such as cardiac myocytes. Mitochondria are eliminated via mitochondrial autophagy or mitophagy. In the heart, mitophagy is an essential housekeeping process and required for cardiac homeostasis. Reduced autophagy and accumulation of impaired mitochondria have been linked to progression of heart failure and aging. In this review, we discuss the pathways that regulate mitophagy in cells and highlight the cardioprotective role of mitophagy in response to stress and aging. We also discuss the therapeutic potential of targeting mitophagy and directions for future investigation.